2021
DOI: 10.3354/meps13865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on a mixotrophic dinoflagellate (Lepidodinium sp.) under different nutritional strategies

Abstract: Mixotrophs are widely distributed in aquatic ecosystems and play critical roles in the planktonic food web. However, how mixotrophs respond to projected ocean warming remains a debatable topic. To close the knowledge gap, we investigated the thermal responses of growth rate and functional traits of a mixotrophic dinoflagellate (Lepidodinium sp.) isolated from subtropical coastal waters. We found that Lepidodinium sp. is a facultative mixotroph with an obligate phototrophic lifestyle that adjusts its phagocytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Lepidodinium sp. is a facultative phagotrophic dinoflagellate, of which photosynthesis is obligate and phagotrophy is facultative ( Liu et al, 2021 ). Different from many mixotrophic algae that consume prey when inorganic nutrients are limited, Lepidodinium sp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lepidodinium sp. is a facultative phagotrophic dinoflagellate, of which photosynthesis is obligate and phagotrophy is facultative ( Liu et al, 2021 ). Different from many mixotrophic algae that consume prey when inorganic nutrients are limited, Lepidodinium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Different from many mixotrophic algae that consume prey when inorganic nutrients are limited, Lepidodinium sp. can ingest prey even when nutrients are sufficient for their photosynthesis ( Liu et al, 2021 ). Our study also observed the ingestion behaviours under N Redfiled conditions in which the nutrient concentrations (~20% f/2 medium) did not limit the growth of Lepidodinium sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations